Global prevalence of hepatitis C in general population: a systematic review and meta-analysis - Salari, Nader; Kazeminia, Mohsen; Hemati, Niloufar; Ammari-Allahyari, Mojtaba (Elsevier, 2022)
Background: According to published reports from the World Health Organization, it is estimated that more than 3% of the world's population is infected with HCV. Given the impact of various factors on the prevalence of HCV in the world's population and the lack of general statistics around the world, this study aims to review the studies conducted in this field and statistical analysis of the results of general statistical studies on the prevalence of HCV in the world population. Methods: In this study, systematic review and meta-analysis of information of the studies related to the prevalence of HCV in the world using keywords including: Prevalence, HCV, Hepatitis C, Healthy Population, Healthy subjects, and General Population in SID, MagIran, IranMedex, IranDoc, ScienceDirect, Embase, Scopus, PubMed, Web of Science (WoS) databases and Google Scholar search engine were extracted without time limit until April 2020. In order to perform the analysis of qualified studies, the model of random effects was used, and the inconsistency of studies with I2 index was investigated. Data analysis was performed with Comprehensive Meta-Analysis (Version 2). Results: In a study of 98 studies with a total sample size of 236,964 people in the world, the overall prevalence of HCV was 1.8% (95% CI: 1.4%–2.3%). Also, according to the subgroup analysis in different continents; the highest prevalence of HCV in the African continent was 7.1% (95% CI: 4.4–11.5%). Conclusion: The results of this study show that the prevalence of hepatitis C in the world's population, especially in Africa, is almost high. Therefore, the officials of the World Health Organization should design measures to prevent the spread of this infection.